Reducing fragmentation of primary healthcare financing for more equitable, people-centred primary healthcare - Kara Hanson; Gemini Mtei; Agnes Gatome-Munyua; Susan Sparkes; Martin Sabignoso; Prastuti Soewondo; Pierre Yameogo; Cheryl Cashin (BMJ Global Health)
Despite primary healthcare (PHC) being recognised in global declarations—Alma Ata in 1978 and Astana in 2018—and prioritised in national health strategies, chronic under-resourcing of PHC persists in most low-income and middle-income countries. More public spending is needed for PHC, but macrofiscal and political constraints often limit the ability of governments to allocate more public resources to PHC. Under-resourcing has been compounded by fragmented and rigid funding flows, which are inefficient and may erode equity, quality of care and public trust in PHC.This article explores the drivers of fragmentation in PHC financing—low public spending, which results in over-reliance on external sources to fund critical health interventions, and the proliferation of new financing schemes that do not take a system-wide view or adhere to the principles of universality. It then highlights some of the possible consequences of this fragmentation for the efficiency, equity and effectiveness of service delivery.Four countries—Argentina, Burkina Faso, Indonesia and Tanzania—are used to illustrate practical steps that may be taken to minimise the consequences of fragmentation in PHC financing: (1) consolidating multiple coverage schemes, (2) avoiding further fragmentation, (3) harmonising health purchasing functions and (4) streamlining funding flows to the provider level.The country examples reveal lessons for policy-makers grappling with the consequences of fragmented PHC financing. The paper concludes with a research agenda to generate additional evidence on what works to address fragmentation.